Make Your Own Python Text Adventure A Guide to Learning Programming - Johnson, Phillip (Apress, 2018)
Learn programming with Python by creating a text adventure. This book will teach you the fundamentals of programming, how to organize code, and some coding best practices. By the end of the book, you will have a working game that you can play or show off to friends. You will also be able to change the game and make it your own by writing a different story line, including new items, creating new characters, and more. Make your own Python Text Adventure offers a structured approach to learning Python that teaches the fundamentals of the language, while also guiding the development of the customizable game. The first half of the book introduces programming concepts and Python syntax by building the basic structure of the game. You'll also apply the new concepts in homework questions (with solutions if you get stuck!) that follow each chapter. The second half of the book will shift the focus to adding features to your game and making it more entertaining for the player. Python is often recommended as a first programming language for beginners, and for good reason. Whether you've just decided to learn programming or you've struggled before with vague tutorials, this book will help you get started. .